2002
DOI: 10.3354/cr022129
|View full text |Cite
|
Sign up to set email alerts
|

El Niño-Southern Oscillation effects on peanut yield and nitrogen leaching

Abstract: Peanut growers in north Florida asked for help in managing the crop to increase yield and reduce yield variability, using information on the pattern of large-scale climate. The objectives of this study were to explore at 4 locations in the peanut belt of Florida and southern Georgia the potential for improving peanut crop performance by altering crop management according to the phase of the El Niño-Southern Oscillation (ENSO). The CROPGRO-Peanut model was used to simulate peanut yield responses to climate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…It is important to indicate that the simulated yields are consistent with previous research in Florida (e.g., Cabrera et al, 2007;Mavromatis et al, 2002;Hansen et al, 1998) and with historical data (NASS, 2007). In both datasets, synthetic and historical, it is possible to observe differences in sample means for the alternative ENSO phases.…”
Section: Case Study and Datasupporting
confidence: 78%
See 1 more Smart Citation
“…It is important to indicate that the simulated yields are consistent with previous research in Florida (e.g., Cabrera et al, 2007;Mavromatis et al, 2002;Hansen et al, 1998) and with historical data (NASS, 2007). In both datasets, synthetic and historical, it is possible to observe differences in sample means for the alternative ENSO phases.…”
Section: Case Study and Datasupporting
confidence: 78%
“…Several authors, including Baigorria et al (2008), Hansen (2002), Mavromatis et al (2002), and Jones et al (2000), have reported the effect of climate variability due to ENSO on crop yields in Florida. The ENSO is a climatic phenomenon characterized by changes in the sea surface temperature of the equatorial Pacific Ocean that influences the regional climate.…”
Section: Case Study and Datamentioning
confidence: 99%
“…The dependence of agricultural production variability on ENSO and its application to the forecasting of food production have been investigated in Africa, America, Europe, and South Asia (e.g. Cane et al 1994, Jones et al 2000, Orlove et al 2000, Ferreyra et al 2001, Gimeno et al 2002, Mavromatis et al 2002, Phillips et al 2002, Meza & Wilks 2003, Selvaraju 2003, but few such studies are available on EAM and ENSO in SE Asia or China. Our aims in this study were, to analyze for the major agricultural regions of China, (1) seasonal climate variability associated with EAM and ENSO and (2) the dependence of agricultural production on seasonal climate variability.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in using crop models as research tools for annual yield estimation , for tailoring crop management practices to expected weather (Mavromatis et al 2002), or for yield forecasting , has led to an urgent requirement of daily weather data (i.e. global solar radiation (GSR), maximum (T max ) and minimum (T min ) air temperatures, and rainfall).…”
Section: Introductionmentioning
confidence: 99%